Multiplicity and diversity of Plasmodium vivax infections in a highly endemic region in Papua New Guinea. - Cristian Koepfli; Amanda Ross; Benson Kiniboro; Thomas A Smith; Peter A Zimmerman; Peter Siba; Ivo Mueller; Ingrid Felger (Public Library of Science (PLoS), 2011)
Plasmodium vivax is highly endemic in the lowlands of Papua New Guinea and accounts for a large proportion of the malaria cases in children less than 5 years of age. We collected 2117 blood samples at 2-monthly intervals from a cohort of 268 children aged 1 to 4.5 years and estimated the diversity and multiplicity of P. vivax infection. All P. vivax clones were genotyped using the merozoite surface protein 1 F3 fragment (msp1F3) and the microsatellite MS16 as molecular markers. High diversity was observed with msp1F3 (H(E) = 88.1%) and MS16 (H(E) = 97.8%). Of the 1162 P. vivax positive samples, 74% harbored multi-clone infections with a mean multiplicity of 2.7 (IQR = 1-3). The multiplicity of P. vivax infection increased slightly with age (P = 0.02), with the strongest increase in very young children. Intensified efforts to control malaria can benefit from knowledge of the diversity and MOI both for assessing the endemic situation and monitoring the effects of interventions.